Assessment and Error Analysis of Satellite Soil Moisture Products Over the Third Pole - Zeng, Jiangyuan; Shi, Pengfei; Chen, Kun-Shan; Ma, Hongliang; Bi, Haiyun; Cui, Chenyang (IEEE transactions on geoscience and remote sensing, 2022)
The Tibetan Plateau, known as the "Third Pole" of the world, is extremely sensitive to global climate change. Reliable soil moisture information is essential for understanding the impact of the Tibetan Plateau on the Asian monsoon. The study assessed a total of four satellite soil moisture products, namely the SMAP-SCA (V7), ESA CCI (V0.52), AMSR2 LPRM (V001), and FY-3C (V1) over the Tibetan Plateau using three densely-instrumented soil moisture networks (i.e., Maqu, Naqu, and Pali). Moreover, the possible error sources of these products were thoroughly investigated over the Tibetan Plateau, which had not yet been fully explored in previous studies. The results reveal the ESA CCI (V0.52) and SMAP-SCA (V7) generally perform better in the three networks with higher correlation coefficient ( R ) and lower standard deviation of the difference (STDD) compared to other products. The bias of ESA CCI (V0.52) is demonstrated to be dependent on the GLDAS Noah soil moisture, but it correlates much better with soil moisture measurements and also displays lower STDD value than the GLDAS Noah. SMAP brightness temperatures demonstrate much higher sensitivity to soil moisture than the AMSR 2~C -band and FY-3C X -band measurements regardless of vegetation, surface roughness, and land cover heterogeneity. The auxiliary surface temperature used in SMAP-SCA (V7) also performs better than that used in AMSR2 LPRM (V001) and FY-3C (V1) though it is slightly colder than the ground measurements. These factors contribute to the better performance of SMAP-SCA (V7) soil moisture product compared to other satellite datasets. The AMSR2 LPRM (V001) product produces evidently larger absolute values than ground observations, but it can track the temporal trend of soil moisture in sparsely vegetated areas (Naqu and Pali). The FY-3C (V1) product exhibits some abnormal saturation values in Maqu with the highest vegetation biomass, while it performs better in Naqu and Pali with relatively lower vegetation coverage. The surface temperature derived from AMSR2 LPRM and FY-3C shows large uncertainties over the Tibetan Plateau which may be caused by the limited data used to calibrate the empirical surface temperature models.